Edukasi Literasi Digital Aplikasi Perkantoran bagi Anak pada Lembaga Pembinaan Khusus Anak (LPKA) Kelas II Palangka Raya - Sulistyowati Sulistyowati; Ferdiyani Haris; Norhayati .; Rosmiati .; Sam'ani .; Bayu Pratama Nugroho; Susi Hendartie (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
The 1945 Law has guaranteed the right to education and learning for every child, regardless of the child's condition, including child prisoners. Fulfillment of the right to education for child convicts is also part of the training so that child convicts can return to society and become law-abiding and responsible citizens. The Special Child Development Institution (LPKA) Class II Palangka Raya is a correctional institution for children not only for the Palangka Raya region but for the entire province of Central Kalimantan. LPKA Class II Palangka Raya also carries out the functions and duties of coaching, one of which is the provision of formal and non-formal education for the child prisoners under its guidance. This is what underlies the implementation of the collaboration between LPKA Class II Palangka Raya and STMIK Palangkaraya in the form of community service programs in the form of literacy in office application programs namely Microsoft Word to increase knowledge and abilities based on digital skills which play an important role in developing and preparing children to have a new opportunity after leaving LPKA Class II Palangka Raya. The method of activity carried out is by explaining and practicing directly with the computer equipment used. The purpose of implementing this program is to increase knowledge and skills based on digital skills, in this case, the office application Microsoft Word